Programming Microsoft Composite UI Application Block and Smart Client Software Factory - Platt, David S.; Safari eBooks (Redmond, Wash. : Microsoft Press, 2008)
Presents lessons for building smart-client applications with the Composite UI Application Block and the Smart Client Software Factory.
Includes index.
Electronic reproduction.
Keywords: Application software -- Development -- Computer programs; Microsoft software; Electronic books